Ultrasound for the Anesthesiologists: Present and Future - Abdullah S. Terkawi; Dimitrios Karakitsos; Mahmoud Elbarbary; Michael Blaivas; Marcel E. Durieux (The Scientific World Journal)
Ultrasound is a safe, portable, relatively inexpensive, and easily accessible imaging modality, making it a useful diagnostic and monitoring tool in medicine. Anesthesiologists encounter a variety of emergent situations and may benefit from the application of such a rapid and accurate diagnostic tool in their routine practice. This paper reviews current and potential applications of ultrasound in anesthesiology in order to encourage anesthesiologists to learn and use this useful tool as an adjunct to physical examination. Ultrasound-guided peripheral nerve blockade and vascular access represent the most popular ultrasound applications in anesthesiology. Ultrasound has recently started to substitute for CT scans and fluoroscopy in many pain treatment procedures. Although the application of airway ultrasound is still limited, it has a promising future. Lung ultrasound is a well-established field in point-of-care medicine, and it could have a great impact if utilized in our ORs, as it may help in rapid and accurate diagnosis in many emergent situations. Optic nerve sheath diameter (ONSD) measurement and transcranial color coded duplex (TCCD) are relatively new neuroimaging modalities, which assess intracranial pressure and cerebral blood flow. Gastric ultrasound can be used for assessment of gastric content and diagnosis of full stomach. Focused transthoracic (TTE) and transesophageal (TEE) echocardiography facilitate the assessment of left and right ventricular function, cardiac valve abnormalities, and volume status as well as guiding cardiac resuscitation. Thus, there are multiple potential areas where ultrasound can play a significant role in guiding otherwise blind and invasive interventions, diagnosing critical conditions, and assessing for possible anatomic variations that may lead to plan modification. We suggest that ultrasound training should be part of any anesthesiology training program curriculum.